جرائم الاحتلال الفرنسي في مجال حرية الصحافة في الجزائر - طلحة, الياس (جامعة الوادي - University of Eloued, 2019)
تعرضت الصحافة العربية في الجزائر خلال فترة الاحتلال إلى مختلف أنواع التضييق من السلطات الفرنسية، التي مارست عليها كل أنواع التضييق ماديا ومعنويا، سواء عن طريق نفي أصحابها أو سجنهم أو غلق مقراتهم وتوقيف صحفهم، لكنهم لم يبقوا مكتوفي الأيدي بل كافحوا وضحوا بصحتهم وأموالهم من أجل تحقيق أهدافهم النبيلة المتمثلة في الدفاع عن حقوق المسلمين الجزائريين وتوعيتهم وتعليميهم، متجاوزين بذلك التشريعات القمعية والقرارات الإدارية التعسفية، وهو ما سيتم التطرق إليه بالتفصيل في هذا المقال. Abstruct: During the colonial period, the Arab press in Algeria was subject to various forms of harassment by the French authorities, who exercised all kinds of physical and moral restrictions, either by denying their owners or imprisoning them or closing their offices and banning their newspapers. However, the Algerian press did not remain idle but sacrified their efforts and money in order to achieve their noble objectives of defending the rights of the Algerian Muslims and rise their consciousness and education, bypassing repressive legislation and arbitrary administrative decisions. These points will be discussed in detail in this article.
مقال
Keywords: جرائم، الاحتلال الفرنسي، حرية الصحافة، الجزائر; crimes, French occupation, freedom of the press, Algeria